Achieving Greater HIV Prevention Impact Through CDC's National HIV Behavioral Surveillance System. (1st July 2017) - Wejnert, Cyprian; Raymond, Henry Fisher; Robbins, Taylor; Prejean, Joseph; Hall, H. Irene; McCray, Eugene; Paz-Bailey, Gabriela
Abstract : Abstract: The National HIV Behavioral Surveillance system was designed to monitor risk factors for HIV infection and HIV prevalence among individuals at higher risk for HIV infection, that is, sexually active men who have sex with men who attend venues, persons who recently injected drugs, and heterosexuals of low socioeconomic status living in urban areas. These groups were selected as priorities for behavioral surveillance because they represent the major HIV transmission routes and the populations with the highest HIV burden. Accurate data on the behaviors in these populations are critical for understanding trends in HIV infections and planning and evaluating effective HIV prevention activities. The articles in this supplement illustrate how National HIV Behavioral Surveillance data can be used to assess HIV risk behaviors, prevalence, and service utilization of the populations most affected by HIV in the United States and guide local and national high-impact prevention strategies to meet national HIV prevention goals. Abstract : Supplemental Digital Content is Available in the Text.